Clinical Pharmacology of Clazosentan, a Selective Endothelin A Receptor Antagonist for the Prevention and Treatment of aSAH-Related Cerebral Vasospasm - Juif, Pierre-Eric; Dingemanse, Jasper; Ufer, Mike (Frontiers in Pharmacology, 2021)
Aneurysmal subarachnoid hemorrhage (aSAH) may lead to cerebral vasospasm and is associated with significant morbidity and mortality. It represents a major unmet medical need due to few treatment options with limited efficacy. The role of endothelin-1 (ET-1) and its receptor ETA in the pathogenesis of aSAH-induced vasospasm suggests antagonism of this receptor as promising asset for pharmacological treatment. Clazosentan is a potent ETA receptor antagonist for intravenous use currently under development for the prevention of aSAH-induced cerebral vasospasm. The pharmacokinetics of clazosentan are characterized by an intermediate clearance, a volume of distribution similar to that of the extracellular fluid volume, dose-proportional exposure, an elimination independent of drug-metabolizing enzymes, and a disposition mainly dependent on the hepatic uptake transporter organic anion transport polypeptide 1B1/1B3. In healthy subjects, clazosentan leads to an increase in ET-1 concentration and prevents the cardiac and renal effects mediated by infusion of ET-1. In patients, it significantly reduced the incidence of moderate or severe vasospasm as well as post-aSAH vasospasm-related morbidity and mortality. Clazosentan is well tolerated up to the expected therapeutic dose of 15 mg and, in aSAH patients, lung complications, hypotension, and anemia were adverse events more commonly reported following clazosentan than placebo. In summary, clazosentan has a pharmacokinetic, pharmacodynamic, and safety profile suitable to become a valuable asset in the armamentarium of therapeutic modalities to prevent aSAH-induced cerebral vasospasm.